Extraterritoriality and the Right to Health. The Concept of Core Obligations. - Bach-Golecka, Dobrochna (Polski Przegląd Stosunków Międzynarodowych, 2018)
The article aims at distinguishing and analyzing the extraterritorial obligations of states within the contemporary debate on human rights, with a particular focus upon the right to health. It seems that the recent discussion concerning the concept of extraterritorial obligations has been raised by the challenges of globalization and subsequent modifications on traditional notion of sovereignty in international relations. Thus the idea of extraterritorial obligations is a novel phenomenon in international legal discourse, emerging from the analysis of human rights theorists. One of the most visible output of their concern has been the document adopted in September 2011 entitled Maastricht Principles on Extraterritorial Obligations of States in the Area of Economic, Social and Cultural Rights. While undoubtedly the document is not a formally and legally binding instrument still it may prove conducive to strengthening a future discussion and possible development of legal norms within the field of extraterritorial obligations of states. The intention of the second part of the article is to analyse the content of the right to health as developed in human rights law and to distinguish the realm of the so-called core obligations of states within the basic obligation to ensure the highest attainable standard of health. As a corollary to this aim, the possible extraterritorial obligations of states within the field of health law are being identified. Concluding remarks elaborate upon the prospective development of extraterritorial obligations in international law, and the possible impact of the right to health protection within the process of their emergence.